Review: Józef Węglarz, [Physical Education in Stories. Between Theory and Practice], Oficyna Wydawnicza "Impuls", Kraków 2021 - Eligiusz Madejski (University of Applied Sciences in Tarnow, Poland, 2023)
The reviewed book is included in the reading list showing the problems of school physical education and looking for their effective solution. The preparation of such a study consists, as Maciej Demel (1973, p. 7) wrote, 'in critically attacking the present, overcoming outdated and harmful traditions, undermining authorities, (...) constant anxiety and searching, simultaneous penetration of the current state, its origins and prospects.' The author has prepared the book in a slightly different formula. He presented his anxiety about the future of physical education in stories, which gives the work originality. Józef Węglarz can be counted among the few authors who subjectively, with a bit of sarcasm and humor, reveal the weaknesses of physical education. At the same time, using many years of experience, the author suggests how to solve a given problem...